2010
DOI: 10.1029/2009jd012585
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity changes in a warmer climate

Abstract: [1] Key climate feedback due to water vapor and clouds rest largely on how relative humidity R changes in a warmer climate, yet this has not been extensively analyzed in models. General circulation models (GCMs) from the CMIP3 archive and several higherresolution atmospheric GCMs examined here generally predict a characteristic pattern of R trend with global temperature that has been reported previously in individual models, including increase around the tropopause, decrease in the tropical upper troposphere, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
180
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(212 citation statements)
references
References 46 publications
(74 reference statements)
22
180
0
1
Order By: Relevance
“…3D) shows a 5-10% reduction, i.e., increased relative dryness, throughout most of the troposphere, except in the lower and middle troposphere of the deep tropics, and in the lower troposphere of the extratropics and the polar region. This pattern of RH anomaly has been reported in previous studies in the context of cloud radiation feedback and vertical mixing under global warming (15,34). In this work, we emphasize the physical connection of the RH pattern to changes in the HC.…”
Section: Meridional Outflow and Relative Humiditysupporting
confidence: 50%
See 1 more Smart Citation
“…3D) shows a 5-10% reduction, i.e., increased relative dryness, throughout most of the troposphere, except in the lower and middle troposphere of the deep tropics, and in the lower troposphere of the extratropics and the polar region. This pattern of RH anomaly has been reported in previous studies in the context of cloud radiation feedback and vertical mixing under global warming (15,34). In this work, we emphasize the physical connection of the RH pattern to changes in the HC.…”
Section: Meridional Outflow and Relative Humiditysupporting
confidence: 50%
“…Meanwhile, studies have also shown that even though water vapor is increased almost everywhere as global temperature rises, increased dryness (lack of rainfall and reduced surface relative humidity) is found in observations and in model projections, especially in many land regions around the world (11)(12)(13). Reduction in midtropospheric relative humidity and clouds in the subtropics and midlatitude under global warming have also been noted in models and observations, suggesting the importance of cloud feedback and circulation changes (14)(15)(16). Even though robust global warming signals have been found in changing rainfall characteristics (2,17,18), in the widening of the subtropics, and in the relative contributions of circulation and surface warming to tropical rainfall from climate model projections and observations (19)(20)(21)(22)(23)(24), the dynamical linkages between HC changes and global patterns of moistening and drying have yet to be identified and understood.…”
mentioning
confidence: 92%
“…The extent to which the radiative cooling rate shifts upward with warming has been discussed to some extent in previous studies (Hartmann and Larson 2002;Ingram 2010). The rate of radiative cooling in the free troposphere does not vary strongly in the vertical (e.g., Dopplick 1972;Hartmann et al 2001), and thus the most important issue is whether the upper limit of the region of strong radiative cooling shifts vertically in accordance with the transformation.…”
Section: Radiationmentioning
confidence: 99%
“…Studies with general circulation models (GCMs) forced with increasing greenhouse gas concentrations have found an upward shift in the static stability profile (Kushner et al 2001), transient kinetic energy and momentum flux (Lorenz and DeWeaver 2007), relative humidity (Sherwood et al 2010), large-scale condensation rate (O'Gorman and Schneider 2008), and cloud fraction (Mitchell and Ingram 1992). Studies with cloudsystem-resolving models have also found upward shifts in response to warming, including upward shifts in the vertical velocities and distributions of cloud water and ice as the sea surface temperature is increased (Tompkins and Craig 1999;Kuang and Hartmann 2007;Muller et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the radiative transfer (Hartmann, 2002;Soden and Held, 2006;Bony et al, 2006), the large-scale circulation (Sherwood et al, 2010), cloud formation (Luo and Rossow, 2004), precipitation (Bretherton et al, 2004) and stratospheric chemistry (Fueglistaler et al, 2009). The water cycle strongly controls various feedback mechanisms of the Earth system in response to perturbations of the energy balance of the troposphere, such as cloud and ice/snow-albedo feedbacks.…”
Section: Introductionmentioning
confidence: 99%